Functional Analyses of Peripheral Auditory System Adaptations for Echolocation in Air vs. Water - Ketten, Darlene R.; Simmons, James A.; Riquimaroux, Hiroshi; Simmons, Andrea Megela (Frontiers in Ecology and Evolution, 2021)
The similarity of acoustic tasks performed by odontocete (toothed whale) and microchiropteran (insectivorous bat) biosonar suggests they may have common ultrasonic signal reception and processing mechanisms. However, there are also significant media and prey dependent differences, notably speed of sound and wavelengths in air vs water, that may be reflected in adaptations in their auditory systems and peak spectra of out-going signals for similarly sized prey. We examined the anatomy of the peripheral auditory system of two species of bat (big brown bat Eptesicus fuscus, Japanese house bat Pipistrellus abramus) and two toothed whales (harbor porpoise Phocoena phocoena, bottlenose dolphin Tursiops truncatus) using ultra high resolution (11 to 100 micron) isotropic voxel computerized tomography (helical and microCT). Significant differences were found for oval and round window location, cochlear length, basilar membrane gradients, neural distributions, cochlear spiral morphometry and curvature, and basilar membrane suspension distributions. Length correlates with body mass, not hearing ranges. High and low frequency hearing range cut-offs correlate with basilar membrane thickness/width ratios and the cochlear radius of curvature. These features are predictive of high and low frequency hearing limits in all ears examined. The ears of the harbor porpoise, the highest frequency echolocator in the study, had significantly greater stiffness, higher basal basilar membrane ratios, and bilateral bony support for 60% of the basilar membrane length. The porpoise’s basilar membrane includes a “foveal” region with “stretched” frequency representation and relatively constant membrane thickness/width ratio values similar to those reported for some bat species. Both species of bats and the harbor porpoise displayed unusual stapedial input locations and low ratios of cochlear radii, specializations that may enhance higher ultrasonic frequency signal resolution and deter low frequency cochlear propagation.